The effect of climatic conditions on the establishment of localised constant (K) methane generation rate for simulated major waste components in Shah Alam, Selangor, Malaysia - Mohd Yasim, Nurzulaifa Shaheera Erne (2025)
Methane emissions from landfills must be accurately estimated to determine their greenhouse gas emissions and potential for energy generation. Current models, such as LandGEM and IPCC are unable to adapt global climatic conditions and waste compositions, which is their most major limitation. The main goal of this study is to evaluate the effects of Malaysia climatic conditions and waste composition on methane generation rate in landfills. This study used waste characterization and simulated landfill design reactors to investigate methane generation rates for several waste categories including fruit, cooked food, uncooked food, vegetable, paper, textile, garden, plastic, diapers and inorganic waste at an average Malaysian rainfall rate of 4, 10, and 20 mm/day and ambient temperature of 25°C and 37°C. From waste characterisation analysis, cooked food waste with high moisture, volatile solid and carbon content produced more methane than other waste with the value of ultimate methane generation potential (Lo) is 328.39 ml CH4/g VS. Meanwhile, in simulated landfill design reactors, reactor with 100% paper waste produced higher methane with the total methane output is 43.78 L/kg and 91.27 L/kg at 25°C and 37°C respectively. In addition, this study found that high moisture (rainfall) and rising temperatures have a considerable impact on methane generation rates, emphasizing the need of considering these parameters when estimating emissions. To incorporate impacts of climatic conditions and waste composition in estimating localised constant methane generation rate, the lab scale data was analyzed using multiple linear regression (MLR). The backward elimination regression method was selected as the best fitted model with an adjusted R2 of 0.673. In the selected MLR model, only eight out of thirteen independent variables were significant at a=0.1. Thus, the MLR model showed that increasing ambient temperature, percentage of fruit, cooked food, uncooked food, vegetable, textile and garden waste lead to faster deterioration rate, but vice versa result for rainfall. In conclusion, the present MLR model capable in predicting methane generation in Malaysian landfills that received daily rainfall ranging from 4 to 20 mm with ambient temperatures ranging from 25°C to 37°C. In the meantime, this model is available for the 0-100% of six types of waste composition: fruit, cooked food, uncooked food, vegetables, textile, and garden waste. Localised L0 and k values that were obtained from this study are 59.83 m3/Mg and 0.078 y"1 respectively. Moreover, this study allowed to accurately estimate localised methane generation rate in Malaysia landfills.